2005
DOI: 10.1007/s10535-005-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis sativa L. growing on heavy metal contaminated soil: growth, cadmium uptake and photosynthesis

Abstract: The effects of different cadmium concentrations [17 mg(Cd) kg -1 (soil) and 72 mg(Cd) kg -1 (soil)] on Cannabis sativa L. growth and photosynthesis were examined. Hemp roots showed a high tolerance to Cd, i.e. more than 800 mg(Cd) kg -1 (d.m.) in roots had no major effect on hemp growth, whereas in leaves and stems concentrations of 50 -100 mg(Cd) kg -1 (d.m.) had a strong effect on plant viability and vitality. For control of heavy metal uptake and xylem loading in hemp roots, the soil pH plays a central role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 59 publications
6
50
0
6
Order By: Relevance
“…The decreased activity of Rubisco is often correlated with sugars accumulation in leaves (Krapp & Stitt 1995). Linger et al (2005) showed that the accumulation of sugars in the leaves and chloroplasts would generate a considerably downregulation of photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased activity of Rubisco is often correlated with sugars accumulation in leaves (Krapp & Stitt 1995). Linger et al (2005) showed that the accumulation of sugars in the leaves and chloroplasts would generate a considerably downregulation of photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that heavy metal stress can reduce the activity of PS II [15]. The results of this study showed that Cd significantly inhibited the PS II activity, and the Fv/Fm and ETR values were significantly reduced.…”
Section: Discussionmentioning
confidence: 46%
“…One reason is that the high concentration of Cd inhibits the absorption of some elements such as Mg and Fe that are essential for the synthesis of chlorophyll, thus blocking the chlorophyll synthesis [12][13]. In addition, the high concentration of Cd causes the changes in the structure of chlorophyll a, thus affecting its normal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it has been reported previously that heavy metals are not involved in declining the activities of enzymes associated with Calvin cycle, there are enough evidence to say that metal-induced inhibition of enzymes involved in the Calvin cycle is highly responsible for reduced CO 2 assimilation (Romanowska, 2002), in particular, Rubisco and PEPcarboxylase (Mysliwa-Kurdziel et al, 2004). Inhibition of enzyme activities of the Calvin cycle and stomatal closure causing short supply of CO 2 are often reported (Seregin and Ivanov, 2001;Bertrand and Poirier, 2005;Linger et al, 2005). In addition, Barcelo and Poschenrieder (2004) reported that all most all the components of the photosynthetic apparatus, which include chlorophyll and carotenoid content, chloroplast membrane structure, light-harvesting and oxygen-evolving complexes, photosystems and constituents of the photosynthetic electron transport chain are influenced by heavy metals.…”
Section: Role Of Nitric Oxide On Aluminum Toxicitymentioning
confidence: 99%